Pengaruh Kepemimpinan Transformasional dan Kualitas Kehidupan Kerja pada Organizational Citizenship Behavior melalui Komitmen Organisasional - Aisyah, Lilis Nur; Wartini, Sri (Universitas Negeri Semarang, 2016)
Purpose of this research is to explain transformational leadership, quality of work life, and affect on organizational citizenship behavior trhough organizational commitment. The population in this research was all production employee’s PT Ungaran Indah Busana Semarang with of 94 respondents. Method sampling used by proportional stratified random sampling. Method of data collection used questionnaires that measure used a likert scale. The method of analysis in this research used proggame SPSS 21.0 for windows. Result show that transformational leadership to have influence of organizational citizenship behavior amount 0.013, quality of work life to have influence of organizational citizenship behavior amount 0.041, transformational leadership to have influence of organizational commitment amount 0.015, quality of work life to have influence of organizational commitment amount 0.046, and organizational commitment as a mediating variables influence transformational leadership and quality of work life on organizational citizenship behavior mounted to 0.262. Conclusion from this research was more increase of transformational leadership and quality of work life, so it will be increase organizational commitment so it can increased organizational citizenship behavior. Advice for the company is to increased employee motivation at work